(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Runway excursion continues to cause serious deaths and economic losses in aviation. 179 people died in the accidents occurring between 2010 and 2019. The direct cost of accidents in 2019 is estimated at over 4 billion. A new method known as Global Reporting Format (GRF) is introduced after studies carried out by the International Civil Aviation Organization (ICAO) to prevent aircraft accidents caused by runway excursion and to minimize risks associated with it. GRF is considered an important milestone to flight safety by ICAO. In this study, GRF is explained with all its components, and benefits and transition to the application process are discussed. As a result of the study, it is assessed that GRF is a positive contribution to flight safety in the process of take-off or landing by matching information about runway surface conditions obtained to the flight crews especially in adverse conditions.